2015
DOI: 10.18632/oncotarget.5958
|View full text |Cite
|
Sign up to set email alerts
|

MiR137is an androgen regulated repressor of an extended network of transcriptional coregulators

Abstract: Androgens and the androgen receptor (AR) play crucial roles in male development and the pathogenesis and progression of prostate cancer (PCa). The AR functions as a ligand dependent transcription factor which recruits multiple enzymatically distinct epigenetic coregulators to facilitate transcriptional regulation in response to androgens. Over-expression of AR coregulators is implicated in cancer. We have shown that over-expression of KDM1A, an AR coregulator, contributes to PCa recurrence by promoting VEGFA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 99 publications
2
40
0
1
Order By: Relevance
“…However, this notion requires further validation. Our data regarding regulation of KDM5B expression by miR-137 in PTEN null conditions is in clear agreement with earlier studies (28,29). The oncogenic roles of KDM5B are now well explored in prostate cancer; however, information regarding its regulation at both transcriptional and translational levels still remains scarce.…”
Section: Discussionsupporting
confidence: 92%
“…However, this notion requires further validation. Our data regarding regulation of KDM5B expression by miR-137 in PTEN null conditions is in clear agreement with earlier studies (28,29). The oncogenic roles of KDM5B are now well explored in prostate cancer; however, information regarding its regulation at both transcriptional and translational levels still remains scarce.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found that hsa-miR-137 is upregulated in young PCa, while in the literature has been reported downregulated and associated with recurrence following prostatectomy [52]. hsa-miR-137 has a function as an androgen regulated suppressor of androgen signaling by modulating expression of an extended network of transcriptional coregulators [53].…”
Section: Discussionsupporting
confidence: 46%
“…Androgens are essential for normal development of the male gender, and spermatogenesis (Nilsson et al, 2015). Androgen activity is mediated by the androgen receptor (AR), a member of the steroid receptor superfamily (Davis-Dao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%